Transformational change in the Climate Investment Funds: A synthesis of the evidence - Neil Bird; Yue Cao; Adriana Quevedo (Overseas Development Institute (ODI), 2019)
This report is a synthesis of evidence gathered on transformational change within the Climate Investment Funds (CIF). It complements a parallel evaluation on transformational change in the countries where CIF operates. It is distinguished from the evaluation by a focus on the secondary literature, produced both within and outside CIF. The objective of the evidence synthesis is to enhance understanding of how transformational change happens across the CIF portfolio, in a range of country, sector and technology contexts. CIF was established in 2008 to provide scaled-up climate finance to developing countries to support progress towards low-carbon, climate-resilient development. Channelled through multilateral development banks (MDBs), CIF encompasses two funds: the Clean Technology Fund (CTF) and the Strategic Climate Fund (SCF), which includes three targeted programmes - the Forest Investment Program (FIP), the Pilot Program for Climate Resilience (PPCR) and the Program for Scaling Up Renewable Energy in Low Income Countries (SREP). Contributor countries to CIF have pledged more than 8.3 billion to fund preparatory activities and investments in over 70 countries. Two learning questions, developed as part of the CIF Transformational Change Learning Partnership (TCLP) process, guide this evidence synthesis: to what extent and how does CIF's approach to planning, designing and implementing its investments work to advance transformational change? To what extent, how and under what conditions are CIF-supported investments and activities contributing to transformational change?
Keywords: 330